Establishing the Validity of a Cultural Assessment of Suicide Risks in Black Adolescents - Samantha Francois; Leslie Adams; Chavez Phelps (Mental Health Science)
ABSTRACT Although rates of suicide among Black American youth have increased in recent years, few brief assessment tools have been culturally tailored and validated to better identify suicide risk for this population. The current study addresses this gap by testing the validity and reliability of the Cultural Assessment of Suicide Risk‐short form (CARS‐S) in an online sample of Black American adolescents. Three hundred eighty‐one Black adolescents (Mage = 17.5) completed a 13‐item CARS‐S measure online. Cronbach's alpha and exploratory and confirmatory factor analysis were computed in Stata v.15 and Mplus v.8.0. The revised CARS‐S scale demonstrated acceptable internal consistency (Cronbach's α = 0.82). A four‐factor solution retained through exploratory analysis demonstrated the best model fit (χ2 = 46.62, p < 0.001; RMSEA = 0.05, 95% CI = 0.01–0.08 CFI = 0.99; TLI = 0.97) compared to other model solutions. Confirmatory analysis supported a four‐factor model with no cross‐loaded items. The four factors were: (1) Family conflict and idioms of distress‐suicidal actions (four items); Social Support (two items); Minority‐specific distress (three items); Idioms of distress‐emotional/somatic and cultural sanctions (four items). Researchers conducting future suicide prevention research focused on Black American adolescents and including the CAR‐S measure should consider the inclusion of items related to family conflict and racism‐related stress to better capture risk.